Observations of Flux Ropes With Strong Energy Dissipation in the Magnetotail. Issue 2 (24th January 2019) - Huang, S. Y.; Jiang, K.; Yuan, Z. G.; Zhou, M.; Sahraoui, F.; Fu, H. S.; Deng, X. H.; Khotyaintsev, Yu. V.; Yu, X. D.; He, L. H.; Deng, D.; Pollock, C. J.; et al.
Abstract: An ion‐scale flux rope (FR), embedded in a high‐speed electron flow (possibly an electron vortex), is investigated in the magnetotail using observations from the Magnetospheric Multiscale (MMS) spacecraft. Intense electric field and current and abundant waves are observed in the exterior and interior regions of the FR. Comparable parallel and perpendicular currents in the interior region imply that the FR has a non‐force‐free configuration. Electron demagnetization occurs in some subregions of the FR. It is surprising that strong dissipation ( J  ×  E' up to 2, 000 pW/m 3 ) occurs in the center of the FR without signatures of secondary reconnection or coalescence of two FRs, implying that FR may provide another important channel for energy dissipation in space plasmas. These features indicate that the observed FR is still highly dynamical, and hosts multiscale coupling processes, even though the FR has a very large scale and is far away from the reconnection site. Plain Language Summary: Flux ropes, 3‐D helical magnetic structures, in which magnetic field lines twist with each other, play an important role in the macroscopic and microscopic physical process during magnetic reconnection. Most of previous studies focused on the flux ropes in the reconnection region. However, some physical process inside macroscopic flux ropes far away from the reconnection site in the magnetotail is still unclear due to the lack of high time resolution data. In this letter, thanks to the unprecedented high time resolution data of the Magnetospheric Multiscale (MMS) mission, we report an ion‐scale flux rope and study its dynamics. Our observations demonstrate that the observed flux rope is still highly dynamical, and hosting multiscale coupling processes and strong energy dissipation, even though the flux rope has very large scale and is far away from the reconnection site. Key Points: An ion‐scale flux rope, embedded in possible electron vortex, is investigated in the magnetotail in details Electron demagnetization occurs in some subregions of the flux rope, and abundant waves are detected in the exterior and interior regions Strong dissipation occurs in the flux rope, implying that flux rope provides another important channel for energy dissipation in space plasma